PENGARUH LATIHAN MODIFIKASI ZIG-ZAG RUN TERHADAP KELINCAHAN (AGILITY) PEMAIN BLACK PANTHER FC KOTA MALANG - Oktavianus Oktavianus; Sapto Adi; Heri Purnama Pribadi (KORSA: Jurnal Kajian Ilmu Keolahragaan dan Kesehatan, 2023)
Agility in futsal is very necessary because futsal requires high intensity. Black Panther FC Malang City players have a low level of agility so they need zig-zag run modification training to train player agility. The purpose of the study was to determine the effect of Zig-Zag Run Modification Training on Agility of Black Panther FC Malang City Players. The zig-zag run exercise is modified into 6 forms of exercise. The method in this study was pre-experimental with One Group Pretest and Posttest design. The population in this study were Black Panther FC Malang City players totaling 36 people.  Sampling using purposive sampling technique with a sample of 20 players selected based on certain criteria. The modified zig-zag run training program in this study was carried out as many as 16 training sessions. The results of hypothesis testing using Paired sample t-test showed a significant value of 0.000, so it can be concluded that zig-zag run modification training provides an effective influence on the agility of Black Panther FC Malang City players.